2015
DOI: 10.1128/cvi.00397-15
|View full text |Cite
|
Sign up to set email alerts
|

Specific CD4+T-Cell Reactivity and Cytokine Release in Different Clinical Presentations of Leptospirosis

Abstract: dClinical manifestations of leptospirosis are highly variable: from asymptomatic to severe and potentially fatal. The outcome of the disease is usually determined in the immunological phase, beginning in the second week of symptoms. The underlying mechanisms, predictive factors, and individual immune responses that contribute to clinical variations are not well understood. The aim of this study was to determine the specifics of CD4 ؉ T-cell reactivity and cytokine release after stimulation with leptospiral ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 29 publications
1
15
0
1
Order By: Relevance
“…The full-texts of the remaining 43 articles were examined for suitability to the review criteria, and 25 were excluded. After the screening procedure, 18 articles were selected for the systematic review [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Selected articles were published over 18 years from 2000 to 2018.…”
Section: Selected Studiesmentioning
confidence: 99%
“…The full-texts of the remaining 43 articles were examined for suitability to the review criteria, and 25 were excluded. After the screening procedure, 18 articles were selected for the systematic review [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Selected articles were published over 18 years from 2000 to 2018.…”
Section: Selected Studiesmentioning
confidence: 99%
“…Indeed, the production of inflammatory cytokines such as TNF-a by CD4+ T-cells after stimulation with antigens of Leptospira was highest in patients with severe disease (Volz et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies described the mechanisms for the pathogen adaptation to thermal conditions (Eshghi et al, 2015a,b) and tolerance (Petrosova and Picardeau, 2014) outside the mammalian host. In addition, the inflammatory cascades that cause clinical disease (Gasque and Jaffar-Bandjee, 2015;Volz et al, 2015), virulence related proteins factors (King et al, 2014), bacteria-host interactions (Lo et al, 2009;Vieira et al, 2012;Siqueira et al, 2013;Fernandes et al, 2015), organization of the cytoskeletal and cellular in the host protein (Schuller et al, 2015) and defense mechanisms by the host (Werts, 2010) by pathogenic Leptospira have been described. Recent studies also identified leucine-rich repeat proteins that are known to be epitopes mediating antigen interaction (Nitipan et al, 2013), immune response factors in lipoproteins on the outer membrane of L. interrogans (Lin et al, 2010), ion transport mechanisms (Wu et al, 2004) and amino acid metabolism (Krajewska et al, 2016).…”
Section: Mechanisms Of Pathogenesis Biological Mechanismsmentioning
confidence: 99%